2022
DOI: 10.1039/d2ee01797k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh oxygen-doped carbon quantum dots for highly efficient H2O2 production via two-electron electrochemical oxygen reduction

Abstract: Direct electrochemical two-electron oxygen reduction (2eORR) into H2O2 provides a promising alternative for on-site green H2O2 production to the predominant anthraquinone oxidation technology. Oxidized carbon materials have demonstrated their impressive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 53 publications
(95 reference statements)
4
49
1
Order By: Relevance
“…Such O-containing groups play a critical role in the 2e – ORR pathways, which has been verified by theoretical calculations and experiments in many reports. Zhi and co-workers confirmed that the C–O bonds from the ether groups in the carbon quantum dot (CQD) catalyst fabricated by the direct dehydration and carbonization of glucose are the most active sites for the 2e – ORR . The CQD catalyst shows an ultrahigh O content (30.4 atom %) and exhibits an excellent catalytic H 2 O 2 production performance with nearly 100% selectivity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Such O-containing groups play a critical role in the 2e – ORR pathways, which has been verified by theoretical calculations and experiments in many reports. Zhi and co-workers confirmed that the C–O bonds from the ether groups in the carbon quantum dot (CQD) catalyst fabricated by the direct dehydration and carbonization of glucose are the most active sites for the 2e – ORR . The CQD catalyst shows an ultrahigh O content (30.4 atom %) and exhibits an excellent catalytic H 2 O 2 production performance with nearly 100% selectivity.…”
Section: Resultsmentioning
confidence: 97%
“…Zhi and co-workers confirmed that the C−O bonds from the ether groups in the carbon quantum dot (CQD) catalyst fabricated by the direct dehydration and carbonization of glucose are the most active sites for the 2e − ORR. 64 The CQD catalyst shows an ultrahigh O content (30.4 atom %) and exhibits an excellent catalytic H 2 O 2 production performance with nearly 100% selectivity. Wang and co-workers demonstrated by the DFT calculations that the electrons are transferred from carboxyl groups to adjacent carbon, which enhances the adsorption strength toward *OOH intermediates and thus promotes the H 2 O 2 generation with high activity and high selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Further downsizing carbon materials into “quantum dots” can open up the bandgap by creating a quantum confinement effect. [ 46 ] Once the bandgap of carbon is opened (indicated as modified carbon in Figure 4e), the modified carbon can take on the role of the semiconductor, and a space charge region may appear in the modified carbon when it is in contact with a metal or semiconductor. Consequently, an internal electric field can be formed in the metal‐modified carbon Schottky junction or semiconductor‐modified carbon heterojunction.…”
Section: Classification Of the Internal Electric Fieldmentioning
confidence: 99%
“…Table S3 (Supporting Information) lists the contents of different oxygen groups. Oxygen doping in carbon has been known promoting the two-electron ORR to H 2 O 2 , [29][30][31] while PN and GN species have been known promoting the four-electron ORR. [13,31,32] The electron transfer number (n) follows the order COF 800 > COF 900 > COF 700 in both alkaline and acidic electrolyte.…”
Section: Origin Of the Electrocatalytic Performance Enhancementmentioning
confidence: 99%